Berries as a case study for crop wild relative conservation, use, and public engagement in Canada. Issue 6 (4th August 2022) - Migicovsky, Zoë; Amyotte, Beatrice; Ulrich, Jens; Smith, Tyler W.; Turner, Nancy J.; Pico, Joana; Ciotir, Claudia; Sharifi, Mehdi; Meldrum, Gennifer; Stormes, Ben; Moreau, Tara
Abstract : Societal impact statement: Plant biodiversity is fundamental to the future of food security and agriculture. Berries are the most economically important fruit crops in Canada. Within this article, we explore the nutritional, cultural, and botanical importance of berries, including crop wild relatives (plant species that are closely related to domesticated crops) and plants that are significant to Indigenous Peoples. Using berries as a case study, we explore opportunities for the conservation, use, and public engagement of crop wild relatives. Our objective is to lay the groundwork for future collaborative efforts across these diverse plants. Summary: Conservation of plant biodiversity, in particular crop wild relatives including those tended and cultivated by Indigenous Peoples, is critical to food security and agriculture. Building on the 2019 road map for crop wild relatives, we examine berries as a case study for crop wild relative conservation, use, and public engagement. We focus on berries due not only to their economic, cultural, and nutritional importance but also because they are consumed fresh, providing a unique opportunity for individuals and communities to connect with plants. We outline health benefits, geographic distribution, and species at risk for Canadian berries. We describe practices, strategies, and approaches used by Indigenous Peoples to steward berries and emphasize the importance of traditional knowledge. We highlight opportunities for in situ and ex situ berry conservation and use of berries in plant breeding and Indigenous foodways. Our aim is to lay the groundwork for future collaborative efforts in these areas and to showcase berries as a useful case study for conservation of food plant biodiversity and public engagement. Abstract : Plant biodiversity is fundamental to the future of food security and agriculture. Berries are the most economically important fruit crops in Canada. Within this article, we explore the nutritional, cultural, and botanical importance of berries, including crop wild relatives (plant species that are closely related to domesticated crops) and plants that are significant to Indigenous Peoples. Using berries as a case study, we explore opportunities for the conservation, use, and public engagement of crop wild relatives, with the objective of continuing to expand efforts across these diverse plants.